2001
DOI: 10.1128/jvi.75.24.12331-12338.2001
|View full text |Cite
|
Sign up to set email alerts
|

Identification of BV/ODV-C42, an Autographa californica Nucleopolyhedrovirus orf101 -Encoded Structural Protein Detected in Infected-Cell Complexes with ODV-EC27 and p78/83

Abstract: orf101 is a late gene of Autographa californica nucleopolyhedrovirus (AcMNPV). It encodes a protein of 42 kDa which is a component of the nucleocapsid of budded virus (BV) and occlusion-derived virus (ODV). To reflect this viral localization, the product of orf101 was named BV/ODV-C42 (C42). C42 is predominantly detected within the infected-cell nucleus: at 24 h postinfection (p.i.), it is coincident with the virogenic stroma, but by 72 h p.i., the stroma is minimally labeled while C42 is more uniformly locate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
43
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 32 publications
4
43
0
Order By: Relevance
“…Deletion analysis demonstrated that c42 is an essential gene for nucleocapsid assembly, whereas no interruption in viral genomic DNA replication was observed (20). Previous reports also provide evidence that C42 binds to P78/83 in a nucleocapsid-independent manner in infected cells (1). Therefore, we hypothesize that one of the pathways through which C42 participates in BV propagation is via interaction with P78/83.…”
mentioning
confidence: 67%
See 3 more Smart Citations
“…Deletion analysis demonstrated that c42 is an essential gene for nucleocapsid assembly, whereas no interruption in viral genomic DNA replication was observed (20). Previous reports also provide evidence that C42 binds to P78/83 in a nucleocapsid-independent manner in infected cells (1). Therefore, we hypothesize that one of the pathways through which C42 participates in BV propagation is via interaction with P78/83.…”
mentioning
confidence: 67%
“…Multiple sequence comparison showed that the NLS motif in C42, which belongs to the pat4 type, is one of the most conserved sequences in all the homologs of C42 either in group I or group II nucleopolyhedrovirus (1,8). Although the molecular mass of C42 (approximately 41.5 kDa) is very close to the 40-kDa limit, which is the empirical threshold for energy-free diffusion through the nuclear pore (8), the nuclear distribution pattern of C42 is absolutely dependent on the NLS motif at its C terminus.…”
Section: Vol 82 2008mentioning
confidence: 99%
See 2 more Smart Citations
“…A construct of the ODV-EC43 deletion produced BVs, but the virions were non-infectious (Alfonso et al, 2012;Fang et al, 2003Fang et al, , 2009). ODV-EC27 was reported to be a type of viral-encoded cyclin homologue, and could interact with C42 and p78/83 (Belyavskyi et al, 1998;Braunagel et al, 2001). The DNA-binding protein P6.9 was identified in the ODVs of all baculoviruses; the majority of P6.9 was distributed near the inner nuclear membrane, whilst a portion localized in the virogenic stroma throughout the course of infection.…”
Section: Proteins Shared By Seven Identified Baculovirusesmentioning
confidence: 99%